Prognosis of peripartum cardiomyopathy in sub-Saharan Africa (Burkina Faso South-West PPCM register) - Arthur Seghda, Taryètba André; Boro, Théodore; Bambara, Jean Eudes; Cisse, Kadari; Lopez, Andrés Miguel; Samadoulougou, André K; Zabsonre, Patrice (Journal of Cardiology and Cardiovascular Medicine, 2020)
Peripartum cardiomyopathy is one of the curable cardiomyopathy. It’s a severe and frequent disease arising among women of childbearing age. Its evolution in the long-term among some patients leads to chronic heart failure. Our study aims to determine from a prospective cohort, the factors associated with the non-recovery of myocardial function upon 12 months of diagnosis. Sociodemographic, clinical and echocardiographic data were collected at the time of diagnosis and then in months 3, 6 and 12. The outcome was the non-recovery of myocardial function at one year, defined by a left ventricular ejection fraction (LVEF) below 50%. 60 patients were analyzed after 12 months of follow-up. Mortality was about 13.3% and recovery rate of myocardial function reached 42.3%. After logistic regression, delay diagnosis and observance were the factors related to non- recovery of myocardial function.